Analisis Kualitas Pelayanan Pengelolaan Pasar Tradisional Terhadap Kepuasan Pedagang dengan Metode Servqual dan IPA - Malik, Vitrawan; Yulistyari, Eka Indah (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2017)
Traditional markets are places where sellers and buyers meet and are marked by the presence of direct buyer-seller transactions; buildings usually consist of kiosks or outlets, booths, and open bases opened by the seller or a market manager. Merchant satisfaction will be influenced by indicators such as cleanliness, comfort, security, and the availability of adequate traditional market facilities and infrastructure such as access to markets. The purpose of this study is to determine the value of Service Quality (SERVQUAL) and improvement efforts with Importance-Performance Analysis (IPA). The study was conducted by conducting surveys and interviews with traders in Pasar Baru, Cilegon, on legal traders, as many as 2,438 active traders, by drawing a sample of 96 respondents or traders using the Slovin formula. Then the data is collected where the information is processed using the Servqual Method (SERVQUAL) and find out the efforts to improve the quality of service by using Importance-Performance Analysis (IPA). The total value of servqual ((TSQ) â) obtained at -4.90 shows that the variety of traditional market management services has not been entirely satisfactory for the new market traders of Cilegon City because the TSQ value is negative.